Tinjauan Yuridis Terhadap Tindak Pidana Penipuan Jual Beli Tanah (Studi Kasus : Putusan No. 74/Pid.B/2017/Pn Gin) - Ngakan Made Wira Diputra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2021)
Crime on this earth will never end. The most frequent criminal treatment in the community is the crime of fraud related to an object. The crime of fraud has been regulated starting from Article 378 to Article 395 of the Criminal Code. This study aims to examine the criminal sanctions against the crime of fraud in the sale and purchase of land and reveal the judges' considerations against the perpetrators of the crime of fraud in the sale and purchase of land according to the case study: Decision No. 74/Pid.B/2017/PN Gin. This study uses a normative legal research method with a legislation approach and a case study approach. The legal materials used are primary and secondary legal materials collected by library and interview techniques. Furthermore, the research data was processed and analyzed descriptively qualitatively. The results of the study revealed that the criminal sanction applied was in the form of a principal sentence by looking at the indictment of the public prosecutor which applied more to Article 378 of the Criminal Code so that in the case study the defendant was sentenced to a year in prison. The Panel of Judges made this decision after hearing statements from the defendant, victim witnesses, and evidence presented by the public prosecutor